Informal Reasoning Profile of State Senior High School Students in Brebes Regency - Fenny Roshayanti; Ipah Budi Minarti; Ariyat Afriadi (P3M IAI Nusantara Batang Hari, 2021)
This study aims to look at the Informal Reasoning profiles of public high school students in the Brebes Regency. Informal Reasoning is a type of thinking used by students in considering socio-scientific issues, which involves considering causation, pros and cons, and alternatives. The research was conducted at 11 public high schools in Brebes Regency using the Proportionate Stratified Random Sampling method. The research data was obtained through tests in the form of multiple-choice questions and essays that tested students' mastery of Informal Reasoning regarding issues such as HIV-AIDS, GMOs, and cloning. The results showed that 79.64% of students had good Informal Reasoning skills, 18.26% of students had very good abilities, and 2.10% of students had moderate abilities. These results indicate that most high school students in Brebes District have good Informal Reasoning skills in addressing socio-scientific issues. Comparing some of the results of students' Informal Reasoning between schools forms a pattern of possible causal factors, such as teachers' habits in teaching and giving questions, environment, region (rural and urban areas), as well as the availability of facilities and infrastructure.